Mechanical behaviour of corroded strands under chloride attack: A new constitutive law. (17th January 2022) - Franceschini, Lorenzo; Vecchi, Francesca; Tondolo, Francesco; Belletti, Beatrice; Sánchez Montero, Javier
Highlights: Constitutive law for the prediction of stress–strain response of corroded strands. Investigated effects of corrosion on the decay of mechanical properties of strands. Useful correlation between maximum pit depth and cross-sectional loss of a wire. Critical cross-sectional loss values for corroded prestressing strands. Database on available results on corroded prestressing strands. Abstract: The paper presents an experimental and analytical study on the tensile behaviour of naturally corroded prestressing strands. A total of twenty-four strands were extracted from full-scale beams which were exposed during 10 years to chlorides from sea water. Firstly, a database has been created on the dependency of the maximum pit depth on the strand mass loss or on the section loss of the most corroded wire. Secondly, the morphology of corrosion pits and the maximum cross-sectional loss of each external wire have been measured. Finally, based on conducted tensile tests, a new constitutive law (CPS-model) is proposed to predict the mechanical behaviour of prestressing strands induced by pitting corrosion.